Controlador para un sistema de potencia redundante de un inversor multinivel de once niveles - Guavita Peralta, Juan Camilo (2018)
This paper presents a novel control strategy for isolated multilevel inverters. This converter has been chosen due to the autonomy of each full bridge. Other advantage is the feasibility of handling the power by cell when there are changes in the batteries state of charge (SOC). In order to take advantage of these benefits, a control strategy has been developed. The main goal of the proposed solution is to change the power produced by each inverter in function of SOC, guaranteeing a proper regulation of the overall power, without affecting the parameters of quality of the output voltage like harmonic distortion and amplitude. The designed solution was tested by power sources variations, finding the control strategy appropriate to accomplish the objective, to modify the power produced by each full bridge in function of SOC without changing overall power of the system and keeping the output voltage constant.